2022
DOI: 10.1289/ehp9889
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Environmental Exposures and Mental Health: Setting an Agenda

Abstract: Background: To date, health-effects research on environmental stressors has rarely focused on behavioral and mental health outcomes. That lack of research is beginning to change. Science and policy experts in the environmental and behavioral health sciences are coming together to explore converging evidence on the relationship—harmful or beneficial—between environmental factors and mental health. Objectives: To organize evidence and catalyze new findings, the National A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 118 publications
0
17
0
Order By: Relevance
“…For example, children in environmental justice communities may be exposed to higher levels of traumatic experiences, such as racial discrimination and environmental disasters ( Jones Harden and Slopen, 2022 ). Furthermore, these communities may have less access to protective factors, such as greenspaces, healthy foods, quality healthcare and other neighborhood amenities ( Reuben et al, 2022 ). It’s essential to understand the degree to which children in environmental justice communities are at increased risk and to what extent chemical exposures contribute to adverse physical health and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, children in environmental justice communities may be exposed to higher levels of traumatic experiences, such as racial discrimination and environmental disasters ( Jones Harden and Slopen, 2022 ). Furthermore, these communities may have less access to protective factors, such as greenspaces, healthy foods, quality healthcare and other neighborhood amenities ( Reuben et al, 2022 ). It’s essential to understand the degree to which children in environmental justice communities are at increased risk and to what extent chemical exposures contribute to adverse physical health and mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the impact of environmental chemicals on children’s mental health is critical to promotion of health, wellbeing, and the prevention of disease ( Thoma et al, 2021 ; Reuben et al, 2022 ). Due to the complex nature of both environmental xenobiotic exposures and mental health outcomes, it is difficult to establish causality with epidemiology studies alone.…”
Section: Discussionmentioning
confidence: 99%
“…A person's mental health can be affected due to many reasons, and it is suggested that as more research is being conducted, keeping mental health in focus, it has become clearer that mental health can be affected due to a combination of several factors such as biological, psychological, and environmental (Causes of Mental Illness, 2003). It has also been found that along with climate change and environmental factors, environmental disasters such as contamination in drinking water, ooding, and drought, for example, affect mental health negatively, and some common effects of which are depression, anxiety and posttraumatic stress disorder (PTSD) (Reuben et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They include the lack of access to resources such as adequate housing, exposure to violence, the experience of death and displacement, feelings of inadequacy, and cultural disconnect. 5,8 Environmental stressors may be physical or social. 9 Physical environmental stressors may influence mental health by altering psychosocial processes and affecting a person's biology or neurochemistry.…”
Section: Introductionmentioning
confidence: 99%